PENGARUH EPS, PBV, PER, DAN PROFITABILITY TERHADAP RETURN SAHAM - Evelyn Rachelina, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to analyze the effect of earnings per share, price to book value, price earning ratio, and profitability on stock returns in consumer goods manufacturing companies that listed in the Indonesia Stock Exchange (IDX) at 2015 - 2018. This study uses 108 data from consumer goods manufacturing companies that have been selected through a purposive sampling method. The data used is secondary data that is processed using SPSS Ver. 23. F test results show the independent variable together has a significant effect on the dependent variable. t test results show that earnings per share significantly positif influence stock returns, while prices for book value, price earning ratios and profitability do not have a significant effect on stock returns.